2007
DOI: 10.1634/stemcells.2007-0483
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mcm2 Expression Results in Severe Stem/Progenitor Cell Deficiency and Cancer

Abstract: ABSTRACThomozygous embryos or mouse embryonic fibroblasts, Mcm2 is reduced to approximately one-third of wild-type levels. Despite the fact that these mice develop normally and are asymptomatic as young adults, life span is greatly reduced, with most surviving to only ϳ10 -12 weeks of age. They demonstrate severe deficiencies in the proliferative cell compartments of a variety of tissues, including the subventricular zone of the brain, muscle, and intestinal crypts. However, the immediate cause of death in mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
180
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(203 citation statements)
references
References 45 publications
21
180
1
1
Order By: Relevance
“…Mice developed normally and were viable, but their life span was greatly reduced. Young adults displayed proliferation deficiencies in several tissues and started to die after 10-12 weeks, mostly because of lymphomas (31). These results confirm that a full complement of MCM proteins is required in vivo to maintain genomic integrity and avoid cancer predisposition.…”
Section: Dosage In Metazoansupporting
confidence: 58%
“…Mice developed normally and were viable, but their life span was greatly reduced. Young adults displayed proliferation deficiencies in several tissues and started to die after 10-12 weeks, mostly because of lymphomas (31). These results confirm that a full complement of MCM proteins is required in vivo to maintain genomic integrity and avoid cancer predisposition.…”
Section: Dosage In Metazoansupporting
confidence: 58%
“…In two of our tumors with MCM4 mutations, this association could be defined mechanistically by genomic alteration of the family of MCM2-7 genes (43). Consistent with this hypothesis, prior studies have shown that Mcm protein deficiencies result in high rates of cancer in mouse models (44,45), catastrophic chromosomal rearrangements in human lymphoblasts in culture (46), and complex chromosomal alterations at discrete locations that are consistent with chromothripsis (43).…”
Section: Discussionmentioning
confidence: 58%
“…However, deregulation of the licensing system may also be a primary driver of oncogenesis, at least in some tumour types. For example, over-expression of Cdc6 or Cdt1 have been shown to be oncogenic, and deregulated Mcm7 expression has been linked to tumour formation, progression and malignant transformation in animal models [84][85][86][87][88][89][90]. Oncogenic mutations in genes upstream of the licensing machinery (eg RAS, CYCLINE and CYCLIND1 ) can also impact on tumourigenesis by causing deregulation of the licensing machinery.…”
Section: Dna Replication Licensing and Cancermentioning
confidence: 99%